Analysis of the off-diagonal component of giant magnetoimpedance effect in Co-based (as-cast and stress-annealed) amorphous ribbons. (February 2018) - Ipatov, M.; Chizhik, A.; Mohamed, Abd El-Moez A.; Sánchez, T.; Hernando, B.; Zhukova, V.; Zhukov, A.P.; Domínguez, L.; González, J.
Abstract: We investigated the effect of the application of dc bias current I B on the off-diagonal magnetoimpedance (MI) components at 50 MHz in nearly-zero magnetostrictive Co66.5 Fe3.5 Si12.0 B18.0 amorphous ribbons in as-cast and stress-annealed state. The off-diagonal MI component is anti-symmetrical with near-linear behavior within a certain field interval. For the off-diagonal response, the dc bias current is necessary to eliminate transverse domains present in the ribbon. A highly asymmetry of the off-diagonal dependence with the axial magnetic field was obtained when the bias current is applied along the ribbon. A rather high slope at the zero-field point was obtained, being more pronounced in the stress-annealed samples. This is probably related with the domain structure reorganization under the effect of the bias current. This behavior is ideal for a practical sensor circuit design.